Implementasi Kurikulum Madrasah 2019 pada Pembelajaran Mata Pelajaran Pendidikan Agama Islam di MAN-IC Sorong - Bafadal, Julyadin; Rasyid, Muh Rusdi; Abdillah, Fardan (Al-Riwayah : Jurnal Kependidikan, 2023)
The objectives of this scientific research are: 1) To analyze the implementation of the 2019 Madrasah curriculum in learning Islamic Religious Education subjects at MAN-IC Sorong, West Papua; 2) To describe the supporting and inhibiting factors in the implementation of the 2019 Madrasah Curriculum at MAN-IC Sorong, West Papua. This research uses descriptive qualitative research located at MAN-IC Sorong, West Papua. This research approach is a curricular scientific juridical approach. The primary data source in this research is the PAI-Aqidah Akhlak teacher as the main informant and additional informants, namely the head of MAN-IC Sorong, education staff and students. Secondary data sources in this research are KMA 183 of 2019, Madrasah Curriculum 2019, Aqidah Akhlak textbooks, and documentation. The data collection methods used were observation, interviews and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the 2019 Madrasah Curriculum in learning PAI-Aqidah akhak subjects at MAN IC Sorong, is carried out by planning, implementing and evaluating,